EFISIENSI PEMAKAIAN LISTRIK DENGAN PELATIHAN SAVING ENERGY DI DESA PANEMO - Anggraini, Yussi; Yuniahastuti, Irna Tri (Universitas Negeri Surabaya, 2019)
Energy saving training for housewives is the goal of this community partnership program. Themethod used is various types including discussion, counseling, training and mentoring. The stages ofimplementing this program start from pre-survey, formal surveys, community service activities,partner roles, monitoring, and program evaluation. The subjects in this PKM are the mothers of thevillage PKK panemon sugihwaras bojonegoro. Data analysis uses descriptive analysis. Based on theresearch of the community partnership program, it was found that the knowledge possessed aboutsaving energy was still in the medium category of 46%. This is due to the lack of knowledge ofhousewives related to energy saving and there has never been any socialization about this training.The knowledge gained in this PKM activity includes (1) knowledge of equipment that requireselectricity (2) knowledge of the function of household appliances that require electricity (3)knowledge of the use of electrical energy and knowledge of energy saving methods (4) knowledge ofhow to respond to hazards electricity and (5) knowledge of assistance to people who areelectrocuted. Therefore it can be concluded that the existence of energy saving training for motherspkk can help increase knowledge about energy-saving life in the household.